Using Flipped Learning in Online English Literature Courses in Higher Education Institutions After COVID-19: Methods Towards Sustainability in Higher Education - Awajan, Nasaybah Walid (Forum for Linguistic Studies, 2025)
The study explores the effect of using flipped learning in teaching English Literature courses in higher education institutions. The study focuses on the use of flipped learning in synchronous and asynchronous online courses despite the technological application used. The study is based on the quantitative approach, where a questionnaire was distributed to 37 lecturers of English Literature in different Jordanian universities. These instructors were asked to use flipped learning in their online English literature courses. The results showed that flipped learning helped improve the students’language and content knowledge by providing them with more time to finish the pre-lecture material and more time to prepare for the lectures. It also allows teachers to provide the students with more resources that could be accessible to them at any time. It also shows how the use of flipped learning has increased the engagement of the students on the emotional,behavioral, and cognitive levels.